Identification of Novel Mutations in CDC20: Expanding the Mutational Spectrum for Female Infertility - Zhao, Lin; Guan, Yichun; Meng, Qingxia; Wang, Weijie; Wu, Ling; Chen, Biaobang; Hu, Jijun; Zhu, Jiawei; Zhang, Zhihua; Mu, Jian; Chen, Yao; Sun, Yiming; et al. (Frontiers in Cell and Developmental Biology, 2021)
Oocyte maturation and fertilization are fundamental processes for successful human reproduction, and abnormalities in these processes will cause infertility. Recently, we identified biallelic mutations in CDC20 that are responsible for human oocyte maturation arrest, fertilization failure, and early embryonic development arrest. In this study, we screened for further CDC20 mutations in a new cohort of patients with abnormalities in oocyte maturation, fertilization, and early embryonic development. Through whole-exome sequencing, we identified the four novel mutations c.887G>A (p. Arg296Gln), c.964C>T (p.Arg322*), c.1155G>C (p.Trp385Cys), and c.330+1G>A (p. Glu111Ilefs*36) and one previously reported mutation c.965G>A (p.Arg322Gln) in CDC20 in four infertile individuals from three independent families. The patients had different phenotypes of oocyte maturation arrest and fertilization failure resulting from the different mutations. This study confirms our previous research and expands the spectrum of known mutations in CDC20, providing new evidence supporting the function of CDC20 in the genetic etiology of female infertility characterized by oocyte maturation arrest and fertilization failure.